2023
DOI: 10.1177/08862605231162664
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Relationships Between Adverse Childhood Experiences, Negative Emotional States, and Violent Delinquency

Abstract: Adverse childhood experiences (ACEs) have been linked to a host of negative health and behavioral outcomes, including crime, delinquency, and violence. Recent work on ACEs suggests that the impact of ACEs differs by gender, but research is unclear on the mechanisms of this relationship and how they impact violent delinquency. To explore whether and how the impact of ACEs on violent delinquency varies by gender, this study draws on Broidy and Agnew’s gendered expansion of general strain theory (GST), which prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Clinical data suggests that female SUD forensic psychiatric patients experience certain ACEs (sexual, verbal, and emotional abuse and emotional neglect) more often than men [24,25]. On the other hand, there is some evidence that ACEs affect men more profoundly than women [18], although Pflugradt et al recently demonstrated an increased incidence of ACEs in female murderers [26]. Knowing that ACEs increase the probability of becoming violent offenders [18] and developing other health issues [16,17], this may still explain why violent index crimes are more prominent in male forensic psychiatric patients [24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Clinical data suggests that female SUD forensic psychiatric patients experience certain ACEs (sexual, verbal, and emotional abuse and emotional neglect) more often than men [24,25]. On the other hand, there is some evidence that ACEs affect men more profoundly than women [18], although Pflugradt et al recently demonstrated an increased incidence of ACEs in female murderers [26]. Knowing that ACEs increase the probability of becoming violent offenders [18] and developing other health issues [16,17], this may still explain why violent index crimes are more prominent in male forensic psychiatric patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is some evidence that ACEs affect men more profoundly than women [18], although Pflugradt et al recently demonstrated an increased incidence of ACEs in female murderers [26]. Knowing that ACEs increase the probability of becoming violent offenders [18] and developing other health issues [16,17], this may still explain why violent index crimes are more prominent in male forensic psychiatric patients [24]. However, our current findings suggest that physical abuse during childhood and youth adds very little to no prognostic value regarding violent reoffending or the duration until criminal recidivism in both female patient populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Countering Leban and Gibson's (2020) and Gajos et al's (2023) results, Pierce and Jones (2022) and Leban and Delacruz (2023) found that ACEs were associated with delinquent behavior among adolescent girls. Pierce and Jones (2022) used data from the Future of Families study and found that girls who experienced two or more ACEs by age nine were more likely to report delinquent behavior in later adolescence as compared to boys (Pierce & Jones, 2022).…”
Section: Race and Sex Differences In The Aces Afv Relationshipsmentioning
confidence: 90%